2021
DOI: 10.1091/mbc.e20-11-0699
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid flippases and Sfk1 are essential for the retention of ergosterol in the plasma membrane

Abstract: Sterols are important lipid components of the plasma membrane (PM) in eukaryotic cells, but it is unknown how the PM retains sterols at a high concentration. Phospholipids are asymmetrically distributed in the PM, and phospholipid flippases play an important role in generating this phospholipid asymmetry. Here, we provide evidence that phospholipid flippases are essential for retaining ergosterol in the PM of yeast. A mutant in three flippases, Dnf1-Lem3, Dnf2-Lem3, and Dnf3-Crf1, and a membrane protein, Sfk1,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 126 publications
(280 reference statements)
2
21
0
Order By: Relevance
“…In reciprocal experiments, we addressed whether the Tcb proteins also regulate sterol availability at the PM (Fig 4F). In wild-type cells, the sterol probe mCherry-D4H (Maekawa & Fairn, 2015;Marek et al, 2020) localised primarily to the daughter bud with relatively low levels observed at the PM of the mother cell (Fig 4F ), consistent with previous reports (Marek et al, 2020;Kishimoto et al, 2021). However, the distribution of the sterol probe was altered in cells lacking the Tcb proteins, with increased mCherry-D4H signal at the PM of the mother cell (~3-fold greater than wild type control cells; Fig 4F).…”
Section: Tricalbins Regulate Phosphatidylserine Distribution Upon Hea...supporting
confidence: 88%
See 4 more Smart Citations
“…In reciprocal experiments, we addressed whether the Tcb proteins also regulate sterol availability at the PM (Fig 4F). In wild-type cells, the sterol probe mCherry-D4H (Maekawa & Fairn, 2015;Marek et al, 2020) localised primarily to the daughter bud with relatively low levels observed at the PM of the mother cell (Fig 4F ), consistent with previous reports (Marek et al, 2020;Kishimoto et al, 2021). However, the distribution of the sterol probe was altered in cells lacking the Tcb proteins, with increased mCherry-D4H signal at the PM of the mother cell (~3-fold greater than wild type control cells; Fig 4F).…”
Section: Tricalbins Regulate Phosphatidylserine Distribution Upon Hea...supporting
confidence: 88%
“…The data also show that the Tcb proteins regulate phospholipid homeostasis at the PM upon stress conditions. Furthermore, we find that Tcb3 co-localises with the PM protein Sfk1, an ortholog of the mammalian TMEM150/FRAG1/DRAM proteins, that is implicated in stress-induced PI(4,5)P 2 synthesis and phospholipid asymmetry at the PM (Audhya & Emr, 2002;Chung et al, 2015;Mioka et al, 2018;Kishimoto et al, 2021). Finally, we find that the Tcb proteins promote the recruitment of Pkc1 to the mother cell cortex upon heat stress conditions.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations